Desogestrel enhances ventilation in ondine patients: Animal data involving serotoninergic systems. (August 2016) - Joubert, Fanny; Perrin-Terrin, Anne-Sophie; Verkaeren, Emilienne; Cardot, Philippe; Fiamma, Marie-Noëlle; Frugière, Alain; Rivals, Isabelle; Similowski, Thomas; Straus, Christian; Bodineau, Laurence
Abstract: Congenital central hypoventilation syndrome (CCHS) is a neurorespiratory disease characterized by life-threatening sleep-related hypoventilation involving an alteration of CO2 /H + chemosensitivity. Incidental findings have suggested that desogestrel may allow recovery of the ventilatory response to CO2 . The effects of desogestrel on resting ventilation have not been reported. This study was designed to test the hypothesis that desogestrel strengthens baseline ventilation by analyzing the ventilation of CCHS patients. Rodent models were used in order to determine the mechanisms involved. Ventilation in CCHS patients was measured with a pneumotachometer. In mice, ventilatory neural activity was recorded from ex vivo medullary-spinal cord preparations, ventilation was measured by plethysmography and c-fos expression was studied in medullary respiratory nuclei. Desogestrel increased baseline respiratory frequency of CCHS patients leading to a decrease in their PETCO2 . In medullary spinal-cord preparations or in vivo mice, the metabolite of desogestrel, etonogestrel, induced an increase in respiratory frequency that necessitated the functioning of serotoninergic systems, and modulated GABAA and NMDA ventilatory regulations. c-FOS analysis showed the involvement of medullary respiratory groups of cell including serotoninergic neurons of the raphe pallidus and raphe obscurus nuclei that seem to play a key role. Thus, desogestrel may improve resting ventilation in CCHS patients by a stimulant effect on baseline respiratory frequency. Our data open up clinical perspectives based on the combination of this progestin with serotoninergic drugs to enhance ventilation in CCHS patients. Highlights: Desogestrel enhances basal ventilation in Ondine's curse. Etonogestrel increased respiratory frequency by medullary mechanisms. GABAA and NMDA receptors are involved in the respiratory effect of etonogestrel. 5-HT systems are implicated on the effect of etonogestrel on basal ventilation. Combining 5-HT and desogestrel may constitute a therapeutic utility in Ondine's curse.